Racism and Islamophobia in the Discursive Market of the Spanish Left - Gil-Benumeya Flores, Daniel (Política y Sociedad, 2021)
Despite the assumption that the Left is in itself anti-racist, in discourses and political practice of the Spanish Left, the fight against racism has often had a limited space that only expands in a temporary way, and its presence has been even more marginal in analytical literature. Islamophobia, a form of specific racism against Muslim people or considered as such, has not received particular attention. The political space after 15 M has inherited these characteristics. However, since recent times, there has been a greater interest in racism and anti-racism in the discursive market of the left, as well as an incipient interest in islamophobia, due to a series of factors analyzed in this article according to the internal logic of both the political field and the specific field of leftist activism.